Implementation of the Binmas Apparatus application to improve the performance of the Kuningan Police Department’s bhabinkamtibmas in the context of promoting public services - Hutama, Adhibya Pramudito (Police Studies Review, 2024)
Technological developments that have an impact on social life have made Korbinmas Polri innovate to create the Binmas Aparat application that is used by bhabinkamtibmas for services to the community by using Android and iOS-based on smartphones. The Public Service Binmas was created to support the PROMOTER Polri by enhancing the quality of internal Polri by Information Technology-based. The research objectives are (1) knowing the application of the Binmas Aparat by bhabinkamtibmas, (2) What are the obstacles and inhibited factors of the Binmas Aparat application, (3) Efforts that carry out to improve the Binmas Aparat application. To discuss and explore all the things that findings during the research, the author uses management theory, the concept of policy implementation and the concept of public service management. This research was conducted in the Kuningan police jurisdiction with a qualitative approach and research focus on the personel’s performance of Bhabinkamtibmas. Data collection is done by interviewing, observing, and studying documents and using triangulation to insure the truth for drawing conclusions. From doing the research the author found (1) there are still many personnel who have not used the Binmas Aparat application because of the limited facilities and infrastructure provided, (2) outside of the limitations of facilities and infrastructure, the Binmas Aparat application itself is still not applicable in addition to the conventional reporting system of members of the bhabinkamtibmas through the Kuningan Police Whatsapp group, (3) The lack of Korbinmas support, especially in terms of facilities, infrastructure, training and socialization of the Binmas Aparat application Based on the results of the study, the authors suggest that socialization and training be held to all related parties to the application of the Binmas Aparat, and the fullfilled all of facilities and infrastructure to the implementer, in this case the binmas units throughout the Polres, especially the Kuningan Polres, to personnel of Bhabinkamtibmas so as to increase performance motivation and realization Polri’s promoter posture.